The mediating role of self‐esteem in the relationship between hope and life satisfaction among university students during a global health crisis - Stephen Cheong Yu Chan; Qi Lu Huang (Health Science Reports, 2024)
Abstract Background and Aims The worldwide health emergency sparked by the COVID‐19 pandemic has deeply shaken educational environments, posing unprecedented challenges to university students’ well‐being. While individual links between self‐esteem, hope, and well‐being are established, their combined impacts during crises remain underexplored. Our study addresses this gap by investigating the interplay among hope, self‐esteem, and life satisfaction within the context of university students navigating the challenges posed by the pandemic. Methods Conducting an online cross‐sectional self‐administered survey during Hong Kong's third pandemic wave, we measured hope, self‐esteem, and life satisfaction using validated scales. Three hundred and fifteen university students (211 females; mean age = 22.08; SD = 2.74) participated. Results Through multiple regression and mediation analyses, our findings indicate that university students with elevated hope and self‐esteem scored higher on life satisfaction measures. Specifically, our analysis revealed that self‐esteem may serve as a partial mediator in the relationship between hope and life satisfaction, highlighting how heightened hope indirectly enhances life satisfaction by strengthening self‐esteem. Conclusion This study reveals intricate relationships among hope, self‐esteem, and life satisfaction in university students, particularly during external adversities like the COVID‐19 pandemic. The implications extend to mental health interventions, emphasizing the potential benefits of cultivating hope and self‐esteem to enhance life satisfaction among university students confronting formidable challenges.